ADVOKASI KARIR MELALUI TANAMAN HIDROPONIK BAGI NARAPIDANA REHABILITASI DI BAPAS PURWOKERTO - Khoirunnisa; Adelia Cahya; Kholil Lur Rochman (BHAKTISIFA: Jurnal Pengabdian kepada Masyarakat, 2025)
This study aims to analyze the effectiveness of a hydroponic training program implemented by the Class II Purwokerto Correctional Center (Bapas) in improving the skills and independence of correctional clients. The research used a descriptive qualitative approach with data collected through interviews with vocational guidance officers and participating clients. The results indicate that hydroponic training had a positive impact on clients, both in technical skills and in their social readiness to reintegrate into society. Clients reported increased self-confidence, new hopes, and potential for independent entrepreneurship after completing the program. However, the training still faces challenges such as limited funding and program sustainability. Despite these obstacles, the training is considered effective as a form of career advocacy and independence development, aligned with the goals of social rehabilitation in the correctional system.